Does kisspeptin exert a local modulatory effect on bovine ovarian steroidogenesis? - Dareen Mattar; Warakorn Cheewasopit; Moafaq Samir; Phil G Knight (Reproduction and Fertility, 2023)
Kisspeptin, a hypothalamic neuropeptide encoded by the KISS1 gene, has a pivotal role in promoting gonadotrophin-releasing hormone secretion in mammals. Kisspeptin and its receptor (KISS1R) are also expressed in certain peripheral tissues including gonads, suggesting intra-gonadal roles. Such actions at the level of the bovine ovary have not been explored previously. The current aims were to determine whether KISS1 and KISS1R are expressed in the bovine ovary and whether kisspeptin or a kisspeptin antagonist can modulate ovarian steroid production by cultured ovarian cells. Granulosa cells (GC) and theca interna cells (TC) were collected from antral follicles (3–18 mm) categorized into five class sizes. Early, mid and regressing corpora lutea (CL) were also collected for RT-qPCR analysis of KISS1 and KISS1R expression. Bovine TC and GC cultured under both non-luteinizing (serum-free) and luteinizing (serum-supplemented) conditions were treated for 4 days with kisspeptin-10 (10–10–10–6M) or kisspeptin antagonist (kp234; 10–10–10–6M), alone and in combination with either follicle-stimulating hormone (GC), luteinizing hormone (TC) or forskolin (luteinized GC/TC). Steroid secretion (GC: oestradiol, progesterone; TC: androstenedione, progesterone; luteinized GC/TC: progesterone) was measured by ELISA and viable cell number determined by neutral red uptake assay. KISS1 and KISS1R transcripts were detected in TC, GC and CL with significant differences between follicle categories and CL stages. However, neither kisspeptin-10 nor kisspeptin antagonist affected steroid secretion or viable cell number in any of the four ovarian cell culture models. As such, the hypothesis that kisspeptin has a direct intraovarian role to modulate follicular or luteal steroidogenesis, or cell proliferation/survival, is not supported.